1998
DOI: 10.2355/isijinternational.38.1130
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Mechanisms in Vanadium Microalloyed Steels Intended for Long Products.

Abstract: The present work has concentrated on the roles of vanadium, nitrogen and carbon in controlling the microstructures and strength of steels designed for hot rolled long products. Effects of cooling rate and additional microailoying with titanium have also been included. MicrostructuresOptlcal micrographs of the final structures are presented in Fig. 2 for the steel D22whlch was essentlally typical of all the steels with the higher carbon level (-0.220/0 C), irrespective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 0 publications
2
43
0
4
Order By: Relevance
“…However, V-microalloyed steels also exhibit grain refinement through intragranular nucleation of ferrite on VN precipitates partly due to low lattice mismatch of VN with ferrite [11,12]. The addition of N in V microalloyed steel stimulates the precipitation of VN particles and increases their volume fraction [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, V-microalloyed steels also exhibit grain refinement through intragranular nucleation of ferrite on VN precipitates partly due to low lattice mismatch of VN with ferrite [11,12]. The addition of N in V microalloyed steel stimulates the precipitation of VN particles and increases their volume fraction [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that when Ti is present in a steel which contains other microalloying elements such as V and Nb, the Ti addition changes the precipitation of V and Nb, and results in a lower yield strength. [12][13][14][15][16][17][18] Most of the work done so far in the development of the thin slab direct rolling technique has been concerned with the process parameters and there are no reports in the literature on a detailed study of the evolution of microstructure over the entire thin slab direct rolling process. The aim of this project was to investigate microstructural development in V-N and V-Ti-N microalloyed steels during the thin slab direct rolling process.…”
Section: Introductionmentioning
confidence: 99%
“…4, is principally due to precipitation strengthening by V-carbonitride second phase particles. 5,17) As the nitrogen content is increased the precipitation of V(C, N) in basically acicular ferrite and bainitic structure is enhanced and particles become more dispersed.…”
Section: Strengthmentioning
confidence: 99%